Manfaat Brain Gym Bagi Perkembangan Anak Usia Dini Di TK Kanisius Pontianak - Desni Yuniarni (Universitas Muhammadiyah Pontianak, 2018)
ABSTRACTEarly childhood is a gold period which his/her potencies should be developed optimally. The way to optimize their potencies for early childhood is by developing the brain function optimally through the introduction of Brain-Gym since brain is a window to learn and work. Brain-Gym consisting of 26 movements can stimulate the three brain dimensions; those are laterality, focus, and concentration dimensions that support the development of emotional skill, social skill, intellectual ability, and physical ability. In particular, the development of all potencies can be done through updated laterality movement that is balancing right-left brain, related to left and right brain dimensions associating with communication ability. Brain gym can improve learning processes and integrate all areas that related to the learning process, specially for children who are a student of early childhood education. So, the aims for this activity is to improve teacher’s knowledge about brain gym. It is hoped that the teacher can practice the brain gym too. To transfer the knowledge about brain gym to the teacher of early childhood education, we use workshop methods. By using this method, teachers can find out about the benefit of brain gym and can practice it for their student. Finally, brain gym can optimize all aspects of child development and maximize children's ability to learn.Keyword: brain gym, early childhood education